(3CMGOjK GdSff GdCQHYI GdehVhYI HMce GdYdGeI GdCdHGfj QMeg Gddg (B1332 / 1420 (3g` (B/s - (3GdCdHGfj, eMeO fGUQ GdOjfs 1914-1999.; (3GdCdHGfj, eMeO fGUQ GdOjfs 1914-1999; (3GdCdHGfj, eMeO fGUQ GdOjfs 1914-1999; (3GdCdHGfj, eMeO fGUQ GdOjfs 1914-1999.; (3GdfSGFj, CMeO Hf Ydj Hf TYjHs 215-303 (3gLQj(B.s; (3GHf eGLI, eMeO Hf jRjO GdQHYjs 209-273 (3gLQj(B.s; (3GdJQePj, eMeO Hf YjSi Hf ShQIs 209-279 (3gLQj(B.s; (3CHh OGhO, SdjeGf Hf GdCTYK Hf ESMGbs 202-275 (3gLQj(B.s ((3GdQjGV (B:s (3OGQ GHf Gdbje ddfTQ hGdJhRjY ,s (3GdbGgQI (B:s (3OGQ GHf YaGf ddfTQ hGdJhRjY,s, 2004)
(3cJGH (B"(3CMGOjK GdSff GdCQHYI GdehVhYI HMce GdYdGeI GdCdHGfj QMeg Gddg(B" (3GYJfi Hg eMeO TheGf GdQedj jJfGhd GdCMGOjK GdJj CTGQ EdjgG GdYdGeI eMeO fGUQ GdOjf GdCdHGfj aj cJHg, hGdJj hUaJ HCfgG ehVhYI Ch VYjaI aj GdSff GdCQHYI (B((3Sff CHj OGhO, Sff GdJQePj, Sff GdfSGFj, hSff GHf eGLg(B)(3, jgOa GdcJGH Edi JhVjM ehVY Jdc GdCMGOjK aj cJH GdSff, eSJYQVG GdMce YdjgG hab efgL GdCdHGfj aj JUMjM GdCMGOjK hJVYjagG, ceG jbOe GdQedj TQhMG hJYdjbGJ JSdW GdVhA Ydi CgejI GdJMbb ef GdCMGOjK GdefbhdI, jYJHQ gPG GdcJGH eQLYG egeG ddHGMKjf hWdGH GdYde GdegJejf HOQGSI GdMOjK hYdheg, MjK jSGYO Ydi age Gdehba GdYdej ef GdCMGOjK GdJj JfSH ddSff GdCQHYI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3MOjKs -- (3GdCMGOjK GdehVhYIs